2011
DOI: 10.1186/1753-4631-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear changes in the activity of the oxygen-dependent demethylase system in Rhodococcus erythropolis cells in the presence of low and very low doses of formaldehyde

Abstract: The effect of exogenous, highly diluted formaldehyde on the rate of demethylation/re-methylation of veratric acid by the bacteria Rhodococcus erythropolis was studied using electrophoretic and microscopic techniques. The activity of 4-O-demethylase, responsible for accumulation of vanillic acid, and the levels of veratric and vanillic acids were determined using capillary electrophoresis. Formaldehyde was serially diluted at 1:100 ratios, and the total number of iterations was 20. After incubation of the succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 34 publications
(42 reference statements)
2
25
0
Order By: Relevance
“…The graphs show a sinusoidal response dependent upon the different noise levels [136] and a peak value at a specific noise level [135]. Such sinusoidal doseresponse phenomena are similar to the sinusoidal dose-response curves noted for homeopathically-prepared medicines in a bacterial cell metabolism model [126].…”
Section: Salient Signal For the Systemsupporting
confidence: 73%
See 4 more Smart Citations
“…The graphs show a sinusoidal response dependent upon the different noise levels [136] and a peak value at a specific noise level [135]. Such sinusoidal doseresponse phenomena are similar to the sinusoidal dose-response curves noted for homeopathically-prepared medicines in a bacterial cell metabolism model [126].…”
Section: Salient Signal For the Systemsupporting
confidence: 73%
“…The graphs show a sinusoidal response dependent upon the different noise levels [136] and a peak value at a specific noise level [135]. Such sinusoidal doseresponse phenomena are similar to the sinusoidal dose-response curves noted for homeopathically-prepared medicines in a bacterial cell metabolism model [126].In statistical physics, Joshi has also shown that weak coupling in a double quantum dot system can exhibit stochastic resonance [138]. A substantial proportion of NPs in at least some homeopathic medicines fall into the quantum dot size range of 1-10 nanometers in diameter [3].…”
supporting
confidence: 72%
See 3 more Smart Citations